Perturbative solutions for compact objects in (2+1)-dimensional Bopp–Podolsky electrodynamics - R. V. Maluf; J. E. G. Silva; C. A. S. Almeida; Gonzalo J. Olmo (European Physical Journal C: Particles and Fields)
Abstract We investigate the space-time geometry generated by compact objects in (2+1)-dimensional Bopp–Podolsky electrodynamics. Inspired by previous studies where the Bopp–Podolsky field acts as a source for spherically symmetric solutions, we revisit this question within the lower-dimensional (2+1) framework. Using a perturbative approach, we derive a charged BTZ-like black hole solution and compute corrections up to second order in a perturbative expansion valid far from the horizon. Our analysis suggests that the near-horizon and inner structure of the solution remain unaltered, indicating that no new non-black hole objects emerge in this regime. In particular, we do not find evidence of wormhole solutions in the (2+1)-dimensional version of this theory.